Impact of mixed plantation strategies on the nutrient concentrations of green and senescent leaves and their nutrient resorption efficiencies in temperate forests of the Loess Hilly Region - Senbao Lu; Senbao Lu; Senbao Lu; Senbao Lu; Yunming Chen; Yunming Chen; Yunming Chen; Jordi Sardans; Jordi Sardans; Josep Peñuelas; Josep Peñuelas (Frontiers in Plant Science)
Mixed-species reforestation/afforestation has been a common practice for improving ecosystem nutrient sustainability. In the Loess Hilly Region, however, it remains unclear whether the mixture of dinitrogen (N2)-fixing species Robinia pseudoacacia with economic species Amygdalus davidiana and Armeniaca sibirica can improve nutrient concentrations of green and senescent leaves and their nutrient resorption. In 2022, we analyzed N and phosphorus (P) concentrations in green (GLNC, GLPC) and senescent leaves (SLNC, SLPC), resorption efficiencies (NRE and PRE), and relative resorption efficiency (RRE) in mixtures of R. pseudoacacia × A. davidiana and R. pseudoacacia × A. sibirica and monocultures of three species, considering tree structure and topsoil (0-20 cm) properties. One-way ANOVA followed by Tukey’s test showed that senescent leaves nutrient concentrations for R. pseudoacacia and Student’s t test that green and senescent leaves of A. davidiana and A. sibirica were significantly greater in mixed stands than monocultures. Based on the same statistical methods, NRE and PRE of R. pseudoacacia varied; those of A. davidiana and A. sibirica were significantly lower in mixed stands than monocultures. Additionally, RRE was < 100% for R. pseudoacacia, but > 100% for A. davidiana and A. sibirica; NRE and PRE was significantly positively associated in A. sibirica and all species. The correlation analysis demonstrated that crown area were significantly positively correlated with N and P concentrations of green and senescent leaves but negatively correlated with NRE and PRE for A. davidiana and A. sibirica, however, they were unrelated for R. pseudoacacia and all species. Further, a random forest model analysis showed that soil available P was main factor driving GLNC for individual rather than all species. Within each species, linear regression analysis revealed that NRE was significantly negatively correlated with SLNC; for A. davidiana and A. sibirica, NRE and PRE were significantly negatively correlated with SLNC and SLPC, respectively. In contrast, the PRE of all species was significantly negatively correlated with GLPC but positively correlated with SLPC. Overall, the results suggested that tree mixture increased N and P cycling more in A. davidiana and A. sibirica than in R. pseudoacacia, in the plant-soil system.